Barroco contemporáneo - Ignacio Iriarte (Orbis Tertius, 2011)
Contemporary Baroque is a category with vague limits. In order to delimit it, two approaches have been proposed. On the one hand, it is stated that Baroque returns since 1900; on the other, that it constitutes a long narrative, dating back to 1600 and continuing up to the present. I here propose an alternative way. Contemporary Baroque is the result of a conceptual shift, developed by the readings that have been made of it from the eighteenth century onwards. In the first part, I briefly retrace this development. In the second part, I establish two periods in order to understand Hispanic American Baroque in the twentieth century